2017
DOI: 10.1016/j.ultsonch.2016.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic cavitation induced generation of stabilizer-free, extremely stable reduced graphene oxide nanodispersion for efficient delivery of paclitaxel in cancer cells

Abstract: Graphene is one of the highly explored nanomaterials due to its unique and extraordinary properties. In this study, by utilizing a hydrothermal reduction method, graphene oxide (GO) was successfully converted to reduced graphene oxide (RGO) without using any toxic reducing agents. Following this, with the use of ultrasonic cavitation, profoundly stable few layer thick RGO nanodispersion was generated without employing any stabilizers or surfactants. During ultrasonication, shockwaves from the collapse of bubbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…This increased stability of rGO-PEG-NH 2 to mechanical stimuli could be justified by the relative lack of defects and functionalities of the reduced graphene layer, that could strengthen the carbon sheet framework. Nonetheless, common features of 2D carbon nanomaterials, such as wrinkles and overall irregularity persisted for the three materials, so they could continue to support the adsorption of ssDNA [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This increased stability of rGO-PEG-NH 2 to mechanical stimuli could be justified by the relative lack of defects and functionalities of the reduced graphene layer, that could strengthen the carbon sheet framework. Nonetheless, common features of 2D carbon nanomaterials, such as wrinkles and overall irregularity persisted for the three materials, so they could continue to support the adsorption of ssDNA [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accompanied strong production of ROS in mitochondria was also observed (Figure 6C), which could react on the total growth of ROS in cells and the vicious circle of mitochondrial damage in turn. We further investigated the relative contribution of PTT on ROS generation and mitochondrial damage, while our results showed that PTT alone did not signi cantly increase ROS or injury mitochondria ((Supplemental materials, Figure S14, [15][16][17]. Taken together, our research indicated that PDT seemed to play a powerful role on ROS generation and mitochondrial damage, thus help exert super-additive therapeutic e ciency of PTX@GO-PEG-OSA NSs.…”
Section: Ptt/pdt Effects Induced By Go-peg-osa Nss Could Combat Drug mentioning
confidence: 77%
“…As is known, polyethylene glycol (PEG) is one of the most frequently-used reagents in biology owing to its high solubility in organic solvents, minimal toxicity and protein-resistance, and PEG-modi ed GO (GO-PEG) nanosheets (NSs) showed higher stability and better biocompatibility [13]. Studies have shown that PTXloaded GO-based nano-DDSs have advantages on improving drug solubility and bioavailability, promoting cytotoxicity to cancer cells through enhanced permeability and retention effect (EPR) and reducing toxic side effects, compared to conventional PTX [15]. Meanwhile, pH-responsive smart drug delivery could help release PTX toward the nucleus and then induce more cancer cells death [16].…”
Section: Introductionmentioning
confidence: 99%
“… The FT-IR spectrum of pristine PTX revealed its characteristic absorption bands of O–H, C–H, CO ester, CO amide, and C–O–C stretching, which appeared at 3438, 2925, 1731, 1646, and 1239 cm –1 , respectively. In addition, its aromatic C–H bending peak emerged at 710 cm –1 (Figure A) . Most of these peaks of PTX remained unchanged in the FT-IR spectra of β–PTX–CC–PTX and β–PTX–SS–PTX with few alterations.…”
Section: Resultsmentioning
confidence: 98%